Controlled Aeration Driven by Oxidation-Reduction Potential Affects Ester Profile in Wine Alcohol Fermentation with Different Starter Cultures - S. J. Xue; L. Wang; S. Chen; X. H. Liu; K. Hu; J. Jiang; Y. S. Tao; G. J. Jin (Australian Journal of Grape and Wine Research)
Background and Aims. Aeration, an important operation in winemaking, cannot be controlled accurately based on dissolved oxygen for ester production in wine alcohol fermentation. The following study describes an aeration control method with oxidation-reduction potential (ORP) in alcohol fermentation and investigates its effect on ester production in fermentations with different starter cultures. Methods and Results. The proposed method is based on using ORP as a switch for aeration timing. Different aeration levels driven by ORP were performed in wine alcohol fermentation with different starter cultures including Saccharomyces cerevisiae (Sc), Pichia fermentans (Pf), Hanseniaspora uvarum (Hu), and their mixes (Pf/Sc and Hu/Sc). The accumulated aeration volume, residual sugar concentration, viable cell number, and ester concentration were analyzed. Results showed that aeration levels could be controlled effectively with an ORP value, and aeration with higher ORPs triggered faster sugar utilization in Sc and Hu/Sc fermentation. Pf and Hu survived one day less in their respective cofermentation with aeration when ORP was −100 mV or −50 mV compared to the natural ORP (−150 mV∼−105 mV in Pf/Sc and −141 mV∼−107 mV in Hu/Sc, respectively). Aeration driven by ORP changed ester profiles in cofermentations. With the aeration levels increasing, the proportion of medium-chain fatty acid ethyl esters in the concentration of total esters first increased and then decreased in Hu/Sc fermentation. When ORP was −100 mV in Pf/Sc fermentation, the proportion of higher alcohol acetates to total esters was highest (8.14%), while that of ethyl acetate to total esters was lowest (87.35%). Conclusions. Aeration driven by ORP improved wine ester profiles by increasing the proportion of medium-chain fatty acid ethyl esters or reducing that of ethyl acetate in cofermentations. Significance of the Study. The present study will allow wineries and researchers to optimize the aeration process in alcohol fermentation and develop a scientific aeration strategy to improve the wine ester profile and aroma quality.